Dysregulation of miR‐125b predicts poor response to therapy in pediatric acute lymphoblastic leukemia. Issue 5 (2nd November 2018) - El‐Khazragy, Nashwa; Elshimy, Amal Ali; Hassan, Safaa Shawky; Matbouly, Safa; Safwat, Gehan; Zannoun, Mohamed; Riad, Ramez. A.
Abstract: Background: Acute lymphoblastic leukemia (ALL) is the most well‐known sort of leukemia in children. In spite of favorable survival rates, some patients relapse and achieve a poor outcome. Methods: We analyzed miR‐125b and Bcl‐2 expressions in pediatric patients with ALL and evaluated their clinical utility as molecular markers for the prediction of disease outcomes. Results: Downregulation of miR‐125b and increased Bcl‐2 expression levels in pediatric patients with ALL were associated with poor prognosis at diagnosis. At day 28 of induction, miR‐125b was significantly increased, whereas Bcl‐2 was downregulated. Loss of miR‐125b during diagnosis and its elevation after therapy are strongly correlated with short leukemia‐free survival and worse survival. Moreover, the combination of miR‐125b with Bcl‐2 markers can clearly enhance the prediction of the disease outcome. Finally, a univariate analysis highlighted the independent prognostic value of miR‐125 in a pediatric patient with ALL. Conclusions: miR‐125b and Bcl‐2 together are potent predictors for the prognosis and, therefore, can be used as therapeutic targets in childhood ALL. Abstract : Acute lymphoblastic leukemia (ALL) is the most well‐known sort of leukemia in children. In spite of favorable survival rates, some patients relapse and achieve a poor outcome. We observed that downregulation of miR‐125b and increased Bcl‐2 expression levels in pediatric patients are potent predictors for the prognosis of disease; therefore, theoretically, they can be used as therapeutic targets in childhood ALL.